Perlindungan Hukum Terhadap Hak Hak Masyarakat Desa dalam Konteks Pemerintahan Desa - Sholichudin Sholichudin; M. Syahrul Borman; Subekti Subekti (Majelis: Jurnal Hukum Indonesia, 2024)
This research aims to analyze legal protection for village people in the village government context in Indonesia. As a government entity that is located in the country on the frontline of the regional autonomy, village has a strategic role in ensuring its fulfillment hak-hakwarga which includes the right to atas public action, paparticipants in the decision-making process, as well as hakatas sustainable development of millions of people. This research uses a normative juridical approach by analyzing the laws and regulations in force, including Law No. 6 of 2014 concerning Villages, andvarious other related regulations. The results of the research show that even though it's a monkey the law that ang adahas provided protection for the village community, there are still gaps in the village lam perpetratornanannya which requires more attention, especially associated withan increase intankapasitasaparavillage tour andnobservationwasan by the governmenthanderah. This research concludes that increasing the effectiveness of legal protection for rural areas requires antarasynergy governmenth village, governmenthdaerah, andnmasyarakat itself.